GIS-material for the archaeological project: Öninge - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned construction of a camping site within the property Öninge 2:2, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a stage 2 survey to decide whether the area contains any unmarked archaeological remains. There is a burial ground and several cup mark sites in the surrounding area. Test trenches were dug on potential settlement sites within the development area. Four scattered and diffuse features were discovered, but were estimated to have little importance for the understanding of the area. The features could not be connected to the burial ground, nor to the cup mark sites. UV Öst is of the opinion that the area does not contain any archaeological remains that give cause for further archaeological investigations.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the survey was to investigate whether the development area contains any archaeological remains.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Fastighetsägaren inom Öninge 2:2 planerar att nyanlägga en campingplats på delar av sin mark, varför Riksantikvarieämbetet UV Öst har utfört en arkeologisk utredning, etapp 2, för att avgöra om exploateringsområdet innehåller omarkerade fornlämningar. Närområdet innehåller bland annat ett gravfält och flera skålgropslokaler. Undersökningen utgjordes av sökschakt på potentiella boplatslägen inom exploateringsytan. Fyra spridda och mycket diffusa anläggningar påträffades men bedömdes ha ringa eller ingen betydelse för områdets förståelse. Anläggningarna kunde inte kopplas till det intilliggande gravfältet eller skålgropslokalerna. UV Öst bedömer att det planerade exploateringsområdet inte innehåller fornlämningar som motiverar fortsatta åtgärder.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen var att avgöra om det planerade exploateringsområdet innehåller fornlämningar.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Öninge
Keywords: stone age; stenålder; Bronze Age; bronsålder; Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi